2020
DOI: 10.3390/plants9070823
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of the Growth and the Active Compounds of Angelica gigas Nakai in Cultivation Sites

Abstract: The active compounds of medicinal plants vary in composition and content depending on environmental factors, such as light, temperature, and soil. According to the Korean Pharmacopoeia standards for herbal medicine, the sum of nodakenin, decursin, and decursinolangelate, which are the marker components of Korean Angelica, should be at least 6.0 g/100 g. However, the content of the components in Korean Angelica cultivated in South Korea often fall below 6.0 g/100 g, due to weather conditions and cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…[ 76 , 77 , 78 , 79 ]. A. gigas Nakai is rich in coumarins mainly nodakenin, decursin, and decursinol angelate [ 80 ]. Bae et al [ 40 ] showed the multi-therapeutic effects of Angelica gigas Nakai extract (AGNE) against NAFLD in mice fed with a high-fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…[ 76 , 77 , 78 , 79 ]. A. gigas Nakai is rich in coumarins mainly nodakenin, decursin, and decursinol angelate [ 80 ]. Bae et al [ 40 ] showed the multi-therapeutic effects of Angelica gigas Nakai extract (AGNE) against NAFLD in mice fed with a high-fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several coumarin derivatives, such as decursins, decursinol, decursinol angelate, nodakenin, nodakenetin, and umbelliferon, have been isolated from A . gigas (Lü et al, 2022; Park et al, 2020). The constituents of A .…”
Section: Angelica Gigasmentioning
confidence: 99%
“…Pyranocoumarins, essential oils, and polyacetylenes are all bioactive components of A. gigas (Zhang et al, 2012). Recently, several coumarin derivatives, such as decursins, decursinol, decursinol angelate, nodakenin, nodakenetin, and umbelliferon, have been isolated from A. gigas (Lü et al, 2022;Park et al, 2020). The constituents of A. gigas are an important ingredient of Ka-mi-kae-kyuk-tang (KMKKT), a formula of ten oriental herbal cocktails that has in vitro and in vivo antitumor properties involving apoptosis, metastasis, and angiogenesis (Lee et al, 2006).…”
Section: Angelica Gigasmentioning
confidence: 99%
“…Cultivation methods only for growth can cause a decrease in the compound contents. Park et al [27] reported that there was a negative correlation (r = − 0.437) between dry weight of root and total contents of active compound (nodakenin, decursin, and decursinol angelate) in Angelica gigas Nakai. And they mentioned that various non-biological stresses can affect the growth of plant or specific functional compounds.…”
Section: Correlation Between Growth Characteristics and Marker Compou...mentioning
confidence: 99%